MEMBANGUN KUALITAS PENDIDIKAN BERMUTU PADA ASPEK KOMPETENSI PAEDAGOGIK DAN KOMPETENSI KEPRIBADIAN BAGI SEORANG CALON GURU - Abdullah, Suhardi (Universitas Khairun, 2016)
The purpose of this article are (1).Â Education process could be shown on the spread of education result that pointed at the experienceÂ effect concerning with the self development (mind), characters and physical ability. (2) education system that should be known of each teacher there are four competences. They are proffessional competence, social competence, individually competence and paedagogic competence. (3) the knowledge that must be mastery consist of the value and moral of scientific that consistent and resposible to the professionality ofÂ teacher duty giude. By this explanation could breakdown as follows, they are (a) a teacher could planned the program learning activities process (b) capability to implemented the learning process and (c) capability for evaluataionKeywords: competence, educated, moral value, and characters.